UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN ACADEMIC SUPERVISION DURING THE COVID-19 PANDEMIC - Rupiah Rupiah (Jurnal As-Salam, 2021)
This study aims to determine the use of information and communication technology (ICT) in academic supervision during the Covid-19 pandemic, its effectiveness, and the obstacles faced. The research method used is a qualitative research method with a descriptive approach. Data was collected using Google Forms. The study results found that academic supervision was implemented by utilizing technology in the form of video call Zoom and Google meet applications. Other applications are also used to conduct discussions without video calls, such as WhatsApp and Telegram. The exciting thing is that school supervisors have used media questions in academic supervision activities. Constraints and solutions are also discussed to find the best solution in the future if academic supervision is still carried out online. The use of technology also has a positive impact in increasing the ability of school supervisors to use technology. Infrastructure improvements in rural areas are needed to ensure signal availability.